ASIC module for MPEG-2 IDCT transformer - Koh, Eng Kiat. (2008)
This thesis presents an ASIC implementation of a 2-D Inverse Discrete Cosine Transform module (2-D IDCT) for MPEG-2 video decoder to meet MP@ML real time requirement.